A high temperature resistant para-aramid spinning oil and preparation method thereof
By using high-temperature-resistant raw materials combinations in aramid spinning oil agent, the problem of volatility and oxidation of oil agents at high temperatures is solved, the high-temperature resistance of oil agents and the reinforcement effect on aramid fibers are improved, and the safety of staff is ensured.
Patent Information
- Application Number
- CN202411471108.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing aramid spinning oil agent is easy to volatilize, oxidize and decompose at high temperatures, resulting in performance changes, affecting the enhancement effect of aramid fibers, and posing a threat to the health of staff.
Pentaerythritol tetraisostearate and/or pentaerythritol tetrastearate are used as smoothing agents, combined with high-temperature-resistant emulsifiers, antioxidants, antistatic agents and bundlers, to form a high-temperature-resistant para-aramid spinning oil agent.
It improves the high temperature resistance and stability of the oil agent, reduces volatilization and oxidative decomposition, enhances the antistatic and bundling properties of aramid fibers, reduces the harm to staff, and improves the oiling effect.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of textile auxiliaries, and more specifically, to a high temperature resistant para-aramid spinning oil and a preparation method thereof. Background Art
[0002] Aramid spinning oil is a chemical additive specially used in the spinning process of aramid fibers. Aramid is a high-performance synthetic fiber with excellent high temperature resistance, chemical corrosion resistance and mechanical properties. In the spinning process, the oil plays a role in lubrication, antistatic and reducing friction between the fiber and the equipment, thereby ensuring the smooth spinning process and improving the quality of aramid fibers.
[0003] The oiling process of aramid spinning is usually divided into two methods: stock solution oiling and solution oiling. Solution oiling is also called emulsion oiling. Stock solution oiling is to directly use oiling agent for oiling, while solution oiling is to dilute the oiling agent with water before oiling. The two oiling methods are suitable for different overall processing production lines of their production enterprises. For example, the subsequent production line of the solution oiling method also needs to add a drying device to dry the water content of the solution after oiling. Compared with solution oiling, the temperature of the aramid spinning reaching the oil tank of the oil agent suitable for the stock solution oiling method is usually relatively high, at about 280°C, and the existing aramid spinning oil agent is mostly organic matter, which is easily volatilized by heat during the processing process, and produces more smoke, which is harmful to the health of the staff. At the same time, the aramid spinning oil agent is prone to property changes at high temperatures, which changes the performance of the oil agent, and then makes the oil agent The reinforcing effect of the aramid fiber is deteriorated. Summary of the invention
[0004] In order to improve the heat resistance of aramid spinning oil, the present application provides a high temperature resistant para-aramid spinning oil and a preparation method thereof.
[0005] In the first aspect, the present application provides a high temperature resistant para-aramid spinning oil, which adopts the following technical solution:
[0006] A high temperature resistant para-aramid spinning oil, comprising the following raw materials in percentage by weight: 50-60% of a smoothing agent, 10-30% of a high temperature resistant emulsifier, 0.5-2% of a high temperature resistant antioxidant, 7-15% of an antistatic agent, 5-10% of a high temperature resistant bundling agent, and 3-7% of a high temperature resistant cosolvent;
[0007] The smoothing agent is pentaerythritol tetraisostearate and / or pentaerythritol tetrastearate; the antistatic agent includes a composite conductive agent, sodium sulfosuccinate and polyethylene glycol oleate in a mass ratio of (0.5-0.7):(1.7-2.2):(1.5-1.8); the composite conductive agent includes modified multi-walled carbon nanotubes and modified composite microspheres in a mass ratio of (1-1.5):(0.9-1.2); the modified composite microspheres are double-layer microspheres, the inner layer of the double-layer microspheres are Al2O3 / TiO2 hollow microspheres, and the outer layer of the double-layer microspheres is polypyrrole.
[0008] By adopting the above technical scheme, the smoothing agent is selected from pentaerythritol tetraisostearate and / or pentaerythritol tetrastearate with high temperature resistance, which not only ensures that the performance of the smoothing agent does not change at high temperature, but also enables the para-aramid spinning oil to have good high temperature resistance. The addition of high temperature resistant antioxidant can reduce the oxidative decomposition rate of the oil at high temperature, further improves the stability of the para-aramid spinning oil at high temperature, and improves the high temperature resistance of the oil. The antistatic agent and the high temperature resistant bundling agent can effectively improve the antistatic and bundling properties of the aramid fiber, reduce the static electricity generated by the aramid fiber during the processing, or the phenomenon of broken wires and adhesion of the aramid fiber during the processing, the high temperature resistance of the oil is improved, the volatilization of the oil during use can be reduced, and the harm to the staff is reduced, and it is beneficial to improve the oiling effect of the oil on the aramid fiber.
[0009] Both sodium sulfonated succinate and polyethylene glycol oleate have good high temperature resistance, are not easy to decompose at high temperature, and have good stability. Sodium sulfonated succinate contains sulfonic acid group and carboxylic acid group, has good hydrophilicity and ionicity, and can form a conductive film, thereby reducing the resistivity of the aramid fiber surface of the material, improving the charge transfer rate, and thus eliminating static electricity; polyethylene glycol oleate can form a thin hydrophilic layer on the surface of the aramid fiber, which can absorb moisture in the environment, thereby reducing the resistivity of the aramid fiber, is beneficial to the charge transfer rate, and reduces the static electricity phenomenon; the composite conductive agent has good conductive properties, can further improve the conductive properties of the oil agent, and then reduce the resistivity of the oil film formed by the oil agent on the surface of the aramid fiber, and reduce the static electricity phenomenon. The composite conductive agent, sodium sulfonated succinate and polyethylene glycol oleate all have good high temperature resistance and good stability at high temperature. They can still have good antistatic properties at the oil agent use temperature, thereby improving the antistatic properties of the aramid fiber after oiling.
[0010] The modified multi-walled carbon nanotubes and the modified composite microspheres both have good electrical conductivity, and can conduct and transfer the static electricity generated by the aramid fibers during the processing, thereby reducing the accumulation of static charge on the surface of the aramid fibers. At the same time, the modified multi-walled carbon nanotubes and the modified composite microspheres have good mechanical properties. After the aramid fibers are oiled with the oil agent, the modified multi-walled carbon nanotubes and the modified composite microspheres can improve the wear resistance and tensile strength of the aramid fibers. The modified multi-walled carbon nanotubes and the modified composite microspheres also have good high temperature resistance, so that the composite conductive agent still has good electrical conductivity at the use temperature of the oil agent, thereby reducing the resistivity of the oiled aramid fibers and improving the antistatic properties of the oiled aramid fibers.
[0011] Alumina and titanium dioxide both have good thermal stability and good hardness. The inner layer of the double-layer microspheres is Al2O3 / TiO2 hollow microspheres, which makes the double-layer microspheres have good thermal stability and mechanical properties, thereby improving the improvement effect of the oil agent on the mechanical properties of aramid fibers. The outer layer of the double-layer microspheres is polypyrrole, which has good conductivity, so that the modified composite microspheres have good antistatic properties. The modified composite microspheres can cooperate with the modified multi-walled carbon nanotubes to further improve the antistatic properties of the oil agent.
[0012] Preferably, the preparation method of the modified multi-walled carbon nanotubes comprises the following steps: adding polyethylene glycol and citric acid modified multi-walled carbon nanotubes to a ferric nitrate solution, stirring evenly, shaking for 2-2.5 hours and slowly adding dilute ammonia water until the solution completely forms a precipitate, washing, drying, and calcining at 450-500° C. to obtain iron-loaded multi-walled carbon nanotubes;
[0013] The iron-loaded multi-walled carbon nanotubes were dispersed in deionized water, and ultrasonic dispersion was performed until uniform dispersion was achieved. Aniline was added and ultrasonic dispersion was performed for 30-35 minutes. The ammonium persulfate aqueous solution was slowly added with stirring in an ice-water bath. After standing for 12 hours, the modified multi-walled carbon nanotubes were filtered, washed, and dried.
[0014] By adopting the above technical scheme, the surface of the multi-walled carbon nanotubes modified with citric acid contains active groups such as carboxyl, hydroxyl and amino groups, which effectively improves the surface activity of the multi-walled carbon nanotubes. Ferric nitrate is used as an iron source. Under the action of ammonia water, the deposition of iron oxide nanoparticles on the surface of the multi-walled carbon nanotubes is achieved through coprecipitation and heat treatment. Aniline is polymerized on the surface of the iron-loaded multi-walled carbon nanotubes under the condition of ammonium persulfate as an initiator, and finally modified multi-walled carbon nanotubes are formed. Polyaniline has good electrical conductivity and can effectively improve the electrical conductivity of the modified multi-walled carbon nanotubes. Iron oxide and polyaniline are composited to form a conductive network, which can further improve the electrical conductivity of the modified multi-walled carbon nanotubes.
[0015] Preferably, the mass ratio of the citric acid-modified multi-walled carbon nanotubes to ferric nitrate is (0.17-0.2):(4.3-5), and the mass ratio of the iron-loaded multi-walled carbon nanotubes to aniline is (1-1.2):(9.5-10.2).
[0016] By adopting the above technical scheme, by controlling the mass ratio of citric acid-modified multi-walled carbon nanotubes to ferric nitrate, and the mass ratio of iron-loaded multi-walled carbon nanotubes to aniline, the contents of iron oxide and polyaniline in the modified multi-walled carbon nanotubes can be effectively controlled. Too high or too low an iron oxide content is likely to affect the conductivity of the modified multi-walled carbon nanotubes, while too high or too low an polyaniline content is likely to affect the conductivity and mechanical properties of the modified multi-walled carbon nanotubes.
[0017] Preferably, the preparation method of the Al2O3 / TiO2 hollow microspheres is: adding polystyrene emulsion to anhydrous ethanol, ultrasonically dispersing it until it is uniform, adding anhydrous ethanol solutions of tetrabutyl titanate and aluminum chloride, mixing them evenly, and then slowly dropping anhydrous ethanol solution containing ammonia water while stirring until the pH is 10-10.2, reacting at 75-80°C for 5.8-6h, centrifuging, washing, and calcining at 480-500°C for 3-3.2h to obtain Al2O3 / TiO2 hollow microspheres.
[0018] By adopting the above technical scheme, polystyrene microspheres are formed using polystyrene emulsion, and tetrabutyl titanate and aluminum chloride are coated on the outside of the polystyrene microspheres. The polystyrene template is removed by calcination to achieve the preparation of Al2O3 / TiO2 hollow microspheres.
[0019] Preferably, the preparation method of the double-layer microspheres is as follows: Al2O3 / TiO2 hollow microspheres are dispersed in deionized water, pyrrole monomer is added, magnetic stirring is performed for 30-40 minutes, and then an aqueous solution of ferric chloride is added, magnetic stirring is performed for 11-12 hours, centrifugation, filtration, washing, and drying are performed to obtain double-layer microspheres.
[0020] By adopting the above technical scheme, pyrrole monomer is uniformly adsorbed on the surface of Al2O3 / TiO2 hollow microspheres, and polymerized under the action of ferric chloride to form a polypyrrole layer. Polypyrrole has good conductive properties and can effectively improve the conductive properties of the double-layer microspheres, thereby improving the antistatic properties of the aramid fiber.
[0021] Preferably, the mass ratio of the Al2O3 / TiO2 hollow microspheres to the pyrrole monomer is (1.8-2.2):(0.42-0.45).
[0022] By adopting the above technical scheme and controlling the mass ratio of Al2O3 / TiO2 hollow microspheres to pyrrole monomers, the thickness of the polypyrrole layer on the outside of the Al2O3 / TiO2 hollow microspheres can be effectively controlled, so that the polypyrrole layer has a good morphology, reduces the self-aggregation and agglomeration of pyrrole, and is beneficial to improving the antistatic properties of the modified composite microspheres.
[0023] In a second aspect, the present application provides a method for preparing a high temperature resistant para-aramid spinning oil, which adopts the following technical solution:
[0024] A method for preparing a high-temperature resistant para-aramid spinning oil comprises the following steps: adding pentaerythritol tetraisostearate and / or pentaerythritol tetrastearate, a high-temperature resistant cosolvent and a high-temperature resistant antioxidant into a reaction kettle, heating to 70-90°C, stirring for 1-2h, cooling to 50-70°C, adding a high-temperature resistant emulsifier, an antistatic agent and a high-temperature resistant sizing agent, stirring until the mixture is uniformly mixed, cooling to room temperature and filtering.
[0025] By adopting the above technical scheme, pentaerythritol tetraisostearate and pentaerythritol tetrastearate both have good high temperature resistance and good lubrication performance, so that the aramid fiber after oiling has good lubrication performance. At the same time, pentaerythritol tetraisostearate and pentaerythritol tetrastearate make the oil agent have good high temperature resistance. The oil agent is not easy to volatilize or decompose during use, reducing the harm to the staff. At the same time, the oil agent has good stability at the use temperature, which is beneficial to improve the oiling effect of the oil agent on the aramid fiber.
[0026] In summary, this application has the following beneficial effects:
[0027] 1. Since the present application adopts pentaerythritol tetraisostearate and pentaerythritol tetraisostearate, pentaerythritol tetraisostearate has good high temperature resistance and lubricity, which not only ensures that the performance of the smoothing agent does not change at high temperature, but also enables the para-aramid spinning oil to have good high temperature resistance. The addition of a high temperature resistant antioxidant can reduce the oxidative decomposition rate of the oil at high temperature, further improve the stability of the para-aramid spinning oil at high temperature, and improve the high temperature resistance of the oil. The antistatic agent and the high temperature resistant bundling agent can effectively improve the antistatic and bundling properties of the aramid fiber, reduce the static electricity generated by the aramid fiber during the processing, or the phenomenon of broken wires and adhesion of the aramid fiber during the processing, and the high temperature resistance of the oil is improved, which can reduce the volatilization of the oil during use, reduce the harm to the staff, and at the same time help to improve the oiling effect of the oil on the aramid fiber;
[0028] 2. In the present application, modified multi-walled carbon nanotubes modified with iron oxide and polyaniline are preferably used. Polyaniline has good electrical conductivity and can further enhance the electrical conductivity of carbon nanotubes. The addition of iron oxide and the composite of iron oxide nanoparticles and polyaniline form a conductive network, which can further improve the electrical conductivity of modified multi-walled carbon nanotubes, thereby improving the antistatic property of the oil.
[0029] 3. In the present application, double-layer microspheres with an inner layer of Al2O3 / TiO2 hollow microspheres and an outer layer of polypyrrole are preferably used. Both alumina and titanium dioxide have good thermal stability and good hardness. The inner layer of the double-layer microspheres is Al2O3 / TiO2 hollow microspheres, which makes the double-layer microspheres have good thermal stability and mechanical properties, thereby improving the improvement effect of the oil agent on the mechanical properties of aramid fibers. The outer layer of the double-layer microspheres is polypyrrole, which has good conductivity, so that the modified composite microspheres have good antistatic properties. The modified composite microspheres can cooperate with the modified multi-walled carbon nanotubes to further improve the antistatic properties of the oil agent. DETAILED DESCRIPTION
[0030] The present application is further described in detail below in conjunction with embodiments.
[0031] Preparation Examples 1-6 of Modified Multi-walled Carbon Nanotubes
[0032] Preparation Example 1
[0033] 1g of pure multi-walled carbon nanotubes was heated and refluxed with ammonia water at 100°C for 2h, washed and dried, dispersed in water, 5g of citric acid was added, ultrasonically dispersed, heated and refluxed at 80°C for 2h, washed and dried, and citric acid-modified multi-walled carbon nanotubes were obtained;
[0034] To 100 mL of 0.043 g / mL ferric nitrate solution, 4.8 g of polyethylene glycol and 0.17 g of citric acid-modified multi-walled carbon nanotubes were added, stirred evenly, shaken for 2.5 h, and 50% by volume of dilute ammonia water was slowly added dropwise until the solution completely formed a precipitate, washed, dried, and calcined at 500 ° C to obtain iron-loaded multi-walled carbon nanotubes;
[0035] 1 g of iron-loaded multi-walled carbon nanotubes was dispersed in deionized water and ultrasonically dispersed until uniformly dispersed. 9.5 g of aniline was added and ultrasonicated for 35 min. 25 ml of 0.5 g / mL ammonium persulfate aqueous solution was slowly added with stirring in an ice-water bath. After standing for 11 h, the modified multi-walled carbon nanotubes were filtered, washed, and dried to obtain modified multi-walled carbon nanotubes.
[0036] Preparation Example 2
[0037] 1g of pure multi-walled carbon nanotubes was heated and refluxed with ammonia water at 100°C for 2h, washed and dried, dispersed in water, 5g of citric acid was added, ultrasonically dispersed, heated and refluxed at 80°C for 2h, washed and dried, and citric acid-modified multi-walled carbon nanotubes were obtained;
[0038] To 100 mL of 0.05 g / mL ferric nitrate solution, 5 g of polyethylene glycol and 0.2 g of citric acid-modified multi-walled carbon nanotubes were added, stirred evenly, shaken for 2 h, and 50% by volume of dilute ammonia water was slowly added dropwise until the solution completely formed a precipitate, washed, dried, and calcined at 450° C. to obtain iron-loaded multi-walled carbon nanotubes;
[0039] 1.2 g of iron-loaded multi-walled carbon nanotubes were dispersed in deionized water and ultrasonically dispersed until uniformly dispersed. 10.2 g of aniline was added and ultrasonicated for 30 min. 20 ml of 0.6 g / mL ammonium persulfate aqueous solution was slowly added with stirring in an ice-water bath. After standing for 12 h, the modified multi-walled carbon nanotubes were filtered, washed, and dried to obtain modified multi-walled carbon nanotubes.
[0040] Preparation Example 3
[0041] The difference between Preparation Example 3 and Preparation Example 1 is that in Preparation Example 3, the concentration of the ferric nitrate solution is 0.03 g / mL.
[0042] Preparation Example 4
[0043] The difference between Preparation Example 4 and Preparation Example 1 is that in Preparation Example 4, the concentration of the ferric nitrate solution is 0.08 g / mL.
[0044] Preparation Example 5
[0045] The difference between Preparation Example 5 and Preparation Example 1 is that in Preparation Example 5, the amount of aniline added is 5 g.
[0046] Preparation Example 6
[0047] The difference between Preparation Example 6 and Preparation Example 1 is that in Preparation Example 6, the amount of aniline added is 12 g.
[0048] Preparation Example 7-12 of Modified Composite Microspheres
[0049] Preparation Example 7
[0050] 0.08 g of polystyrene latex was added to 100 mL of anhydrous ethanol, and ultrasonically dispersed until uniform. 10 mL of anhydrous ethanol solution of 8 wt% tetrabutyl titanate and 4.3 wt% aluminum chloride was added and mixed uniformly. Then, an anhydrous ethanol solution containing 10 wt% ammonia water was slowly added dropwise while stirring until the pH value was 10. The mixture was reacted at 75 °C for 6 h, centrifuged, washed, and calcined at 480 °C for 3.2 h to obtain Al2O3 / TiO2 hollow microspheres.
[0051] 1.8 g of Al2O3 / TiO2 hollow microspheres were dispersed in deionized water, 0.42 g of pyrrole monomer was added, and magnetic stirring was performed for 30 min. Then, 2 mL of 0.62 mol / L ferric chloride aqueous solution was added. After magnetic stirring for 12 h, the mixture was centrifuged, filtered, washed, and dried to obtain double-layer microspheres.
[0052] Preparation Example 8
[0053] 0.08 g of polystyrene latex was added to 100 mL of anhydrous ethanol, and ultrasonically dispersed until uniform. 10 mL of anhydrous ethanol solution of 10 wt% tetrabutyl titanate and 5 wt% aluminum chloride was added and mixed evenly. Then, an anhydrous ethanol solution containing 10 wt% ammonia water was slowly added dropwise while stirring until the pH value was 10.2. The mixture was reacted at 80 °C for 5.8 h, centrifuged, washed, and calcined at 500 °C for 3 h to obtain Al2O3 / TiO2 hollow microspheres.
[0054] 2.2 g of Al2O3 / TiO2 hollow microspheres were dispersed in deionized water, 0.45 g of pyrrole monomer was added, and magnetic stirring was performed for 40 min. Then, 2 mL of 0.6 mol / L ferric chloride aqueous solution was added, and magnetic stirring was performed for 11 h. The mixture was centrifuged, filtered, washed, and dried to obtain double-layer microspheres.
[0055] Preparation Example 9
[0056] The difference between Preparation Example 9 and Preparation Example 7 is that in Preparation Example 9, the concentrations of tetrabutyl titanate and aluminum chloride are 5 wt % and 10 wt %, respectively.
[0057] Preparation Example 10
[0058] The difference between Preparation Example 10 and Preparation Example 7 is that in Preparation Example 10, the concentrations of tetrabutyl titanate and aluminum oxide are 15 wt % and 2 wt %, respectively.
[0059] Preparation Example 11
[0060] The difference between Preparation Example 11 and Preparation Example 7 is that in Preparation Example 11, the mass ratio of Al2O3 / TiO2 hollow microspheres to pyrrole monomer is 1.8:0.2.
[0061] Preparation Example 12
[0062] The difference between Preparation Example 12 and Preparation Example 7 is that in Preparation Example 12, the mass ratio of Al2O3 / TiO2 hollow microspheres to pyrrole monomer is 1.8:0.6. Example
[0063] Example 1
[0064] A high temperature resistant para-aramid spinning oil comprises the following raw materials in percentage by weight: 50% pentaerythritol tetraisostearate, 19% high temperature resistant emulsifier, 2% high temperature resistant antioxidant, 15% antistatic agent, 10% high temperature resistant bundling agent, and 4% high temperature resistant cosolvent; the high temperature resistant temperature is 280°C, the high temperature resistant emulsifier is fatty alcohol polyoxyethylene purchased from BASF Group of Germany, the high temperature resistant antioxidant is antioxidant 1790 purchased from Cytec Industries of the United States, the high temperature resistant bundling agent is Castor oleate was selected and purchased from Zhejiang Royal Madrid Shangyi New Materials Co., Ltd., and the high temperature resistant co-solvent was selected from isomeric octadecyl alcohol, which was purchased from Nanjing Dongde Chemical Technology Co., Ltd. The antistatic agent included a composite conductive agent, sodium sulfonated succinate and polyethylene glycol oleate in a mass ratio of 0.5:1.7:1.5, and the composite conductive agent included modified multi-walled carbon nanotubes and modified composite microspheres in a mass ratio of 1:0.9. The modified multi-walled carbon nanotubes were selected from the modified multi-walled carbon nanotubes prepared in Preparation Example 1, and the modified composite microspheres were selected from the modified composite microspheres prepared in Preparation Example 7.
[0065] The preparation method of the above-mentioned high-temperature resistant para-aramid spinning oil comprises the following steps: adding pentaerythritol tetraisostearate, a high-temperature resistant cosolvent and a high-temperature resistant antioxidant into a reaction kettle, heating to 70°C, stirring for 2 hours, cooling to 50°C, adding a high-temperature resistant emulsifier, an antistatic agent and a high-temperature resistant sizing agent, stirring until uniformly mixed, cooling to room temperature and filtering.
[0066] Example 2
[0067] A high temperature resistant para-aramid spinning oil, comprising the following raw materials in percentage by weight: 55% pentaerythritol tetrastearate, 21.3% high temperature resistant emulsifier, 0.7% high temperature resistant antioxidant, 10% antistatic agent, 7% high temperature resistant clustering agent, 6% high temperature resistant cosolvent; the high temperature resistant temperature is 280°C, the high temperature resistant emulsifier is polyoxypropylene ether, the product is purchased from Nanjing Well Pharmaceutical Group Co., Ltd., the high temperature resistant antioxidant is Swiss Ciba 245, the high temperature resistant clustering agent is The beam agent is CO-10 purchased from Huajie Chemical (Shanghai) Co., Ltd., the high temperature resistant cosolvent is isomeric eicosanol purchased from Sasol of South Africa, the antistatic agent includes a composite conductive agent, sodium sulfonated succinate and polyethylene glycol oleate in a mass ratio of 0.5:1.7:1.5, the composite conductive agent includes modified multi-walled carbon nanotubes and modified composite microspheres in a mass ratio of 1:0.9, the modified multi-walled carbon nanotubes are selected from the modified multi-walled carbon nanotubes prepared in Preparation Example 1, and the modified composite microspheres are selected from the modified composite microspheres prepared in Preparation Example 7.
[0068] The preparation method of the above-mentioned high-temperature resistant para-aramid spinning oil comprises the following steps: adding pentaerythritol tetrastearate, a high-temperature resistant cosolvent and a high-temperature resistant antioxidant into a reaction kettle, heating to 70°C, stirring for 2 hours, cooling to 50°C, adding a high-temperature resistant emulsifier, an antistatic agent and a high-temperature resistant sizing agent, stirring until uniformly mixed, cooling to room temperature and filtering.
[0069] Example 3
[0070] A high temperature resistant para-aramid spinning oil comprises the following raw materials in percentage by weight: 26% pentaerythritol tetraisostearate, 30% pentaerythritol tetrastearate, 25.5% high temperature resistant emulsifier, 0.5% high temperature resistant antioxidant, 7% antistatic agent, 5% high temperature resistant clustering agent, and 3% high temperature resistant cosolvent; the high temperature resistant temperature is 280°C, the high temperature resistant emulsifier is fatty alcohol polyoxyethylene, purchased from Sasol Company of South Africa, the high temperature resistant antioxidant is antioxidant 1790, purchased from Penglai Hongwei Chemical Co., Ltd., The high temperature resistant sizing agent is castor oleate purchased from Shanghai Tiantan Additive Co., Ltd., the high temperature resistant cosolvent is isomeric octadecyl alcohol purchased from Kuala Lumpur Kepong Oil Chemical Co., Ltd., the antistatic agent includes a composite conductive agent, sodium sulfonated succinate and polyethylene glycol oleate in a mass ratio of 0.7:2.2:1.8, the composite conductive agent includes modified multi-walled carbon nanotubes and modified composite microspheres in a mass ratio of 1.5:1.2, the modified multi-walled carbon nanotubes are selected from the modified multi-walled carbon nanotubes prepared in Preparation Example 2, and the modified composite microspheres are selected from the modified composite microspheres prepared in Preparation Example 8.
[0071] The preparation method of the above-mentioned high-temperature resistant para-aramid spinning oil comprises the following steps: adding pentaerythritol tetraisostearate, pentaerythritol tetrastearate, a high-temperature resistant cosolvent and a high-temperature resistant antioxidant into a reaction kettle, heating to 90°C, stirring for 1 hour, cooling to 70°C, adding a high-temperature resistant emulsifier, an antistatic agent and a high-temperature resistant sizing agent, stirring until uniformly mixed, cooling to room temperature and filtering.
[0072] Example 4
[0073] The difference between Example 4 and Example 1 is that in Example 4, in the composite conductive agent, the modified multi-walled carbon nanotubes are the modified multi-walled carbon nanotubes prepared in Preparation Example 3.
[0074] Example 5
[0075] The difference between Example 5 and Example 1 is that in Example 5, in the composite conductive agent, the modified multi-walled carbon nanotubes are the modified multi-walled carbon nanotubes prepared in Preparation Example 4.
[0076] Example 6
[0077] The difference between Example 6 and Example 1 is that in Example 6, in the composite conductive agent, the modified multi-walled carbon nanotubes are the modified multi-walled carbon nanotubes prepared in Preparation Example 5.
[0078] Example 7
[0079] The difference between Example 7 and Example 1 is that in Example 7, in the composite conductive agent, the modified multi-walled carbon nanotubes are the modified multi-walled carbon nanotubes prepared in Preparation Example 6.
[0080] Example 8
[0081] The difference between Example 8 and Example 1 is that in Example 8, in the composite conductive agent, the modified composite microspheres are the modified composite microspheres prepared in Preparation Example 9.
[0082] Example 9
[0083] The difference between Example 9 and Example 1 is that in Example 9, in the composite conductive agent, the modified composite microspheres are the modified composite microspheres prepared in Preparation Example 10.
[0084] Example 10
[0085] The difference between Example 10 and Example 1 is that in Example 10, in the composite conductive agent, the modified composite microspheres are the modified composite microspheres prepared in Preparation Example 11.
[0086] Embodiment 11
[0087] The difference between Example 11 and Example 1 is that in Example 11, in the composite conductive agent, the modified composite microspheres are the modified composite microspheres prepared in Preparation Example 12.
[0088] Comparative Example
[0089] Comparative Example 1
[0090] The difference between Comparative Example 1 and Example 1 is that the weight percentage of each raw material in Comparative Example 1 is: 30% pentaerythritol tetraisostearate, 26% high temperature resistant emulsifier, 2% high temperature resistant antioxidant, 23% antistatic agent, 14% high temperature resistant sizing agent, 5% high temperature resistant cosolvent, and the selection of raw materials is the same as that in Example 1.
[0091] Comparative Example 2
[0092] The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, the composite conductive agent includes modified multi-walled carbon nanotubes and modified composite microspheres in a mass ratio of 1:0.5.
[0093] Comparative Example 3
[0094] The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, the composite conductive agent includes modified multi-walled carbon nanotubes and modified composite microspheres in a mass ratio of 1:2.
[0095] Comparative Example 4
[0096] The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, the antistatic agent includes a composite conductive agent, sodium sulfonated succinate and polyethylene glycol oleate in a mass ratio of 0.5:0.6:2.5.
[0097] Comparative Example 5
[0098] The difference between Comparative Example 5 and Example 1 is that in Comparative Example 5, the antistatic agent includes a composite conductive agent, sodium sulfonated succinate and polyethylene glycol oleate in a mass ratio of 1.5:0.8:1.3.
[0099] Detection Methods
[0100] According to the raw materials and preparation methods of Examples 1-11 and Comparative Examples 1-5, para-aramid spinning oils were prepared, and smoke temperature tests were performed. The test method was based on GBT 382-2017 Kerosene and Jet Fuel Smoke Point Determination Method, and the results were recorded in Table 1.
[0101] After aramid spinning, the above-mentioned para-aramid spinning oil agent was used for stock solution oiling at an oiling temperature of 280°C to obtain aramid treated with the oil agent. The antistatic properties and breaking strength of the treated aramid fiber were tested, and the results are recorded in Table 1.
[0102] Table 1 Para-aramid spinning oil and properties of aramid fibers after treatment
[0103] According to Table 1, Examples 1-3 and Comparative Example 1, it can be seen that the smoke temperature of Examples 1-3 is higher than that of Comparative Example 1, the breaking strength of the aramid fiber treated with Examples 1-3 is higher than that of the aramid fiber treated with Comparative Example 1, and the specific resistance value is lower than that of the aramid fiber treated with Comparative Example 1, indicating that the aramid fiber treated with Examples 1-3 has better antistatic properties and mechanical strength; it indicates that the oil prepared by the raw material ratio of Examples 1-3 has better performance, and at the same time, the amount of pentaerythritol tetraisostearate is reduced in Comparative Example 1. Pentaerythritol tetraisostearate has good heat resistance and lubricity, and reducing its amount causes the heat resistance of the oil of Comparative Example 1 to decrease.
[0104] Pentaerythritol tetraisostearate has good high temperature resistance and lubricity, pentaerythritol tetrastearate has good lubricity and high temperature resistance, thus making the para-aramid spinning oil have good high temperature resistance. The smoothing agent uses pentaerythritol tetraisostearate and / or pentaerythritol tetrastearate with high temperature resistance, which not only ensures that the performance of the smoothing agent does not change at high temperature, but also makes the para-aramid spinning oil have good high temperature resistance. The addition of a reasonable amount of high temperature resistant antioxidant can reduce the oxidation decomposition rate of the oil at high temperature, further improve the stability of the para-aramid spinning oil at high temperature, and enhance the high temperature resistance of the oil. The high temperature resistant emulsifier can further improve the emulsification effect of the oil, thereby improving the oiling effect of the oil on aramid fiber.
[0105] The composite conductive agent formed by the modified multi-walled carbon nanotubes and the modified composite microspheres has good conductivity and can effectively improve the electrostatic charge conduction and transfer performance of the treated aramid fiber. At the same time, the modified multi-walled carbon nanotubes and the modified composite microspheres have good mechanical properties. The modified multi-walled carbon nanotubes and the modified composite microspheres are entangled and connected with each other to form a conductive network, which improves the antistatic performance of the aramid fiber and can effectively improve the mechanical properties of the aramid fiber and enhance its breaking strength. Sodium sulfonated succinate and polyethylene glycol oleate have good high temperature resistance and antistatic performance. The two cooperate with the composite conductive agent to make the aramid fiber have good antistatic performance.
[0106] Compared with Example 1, when preparing modified multi-walled carbon nanotubes in Example 4-5, the concentration of ferric nitrate solution was changed to change the amount of ferric nitrate added. The aramid fiber treated in Example 4-5 had a higher resistivity than the aramid fiber treated in Example 1. The amount of ferric nitrate added directly affected the content of iron oxide in the modified multi-walled carbon nanotubes. Iron oxide was loaded on the surface of the multi-walled carbon nanotubes in the form of nanoparticles, which could effectively improve the conductivity of the multi-walled carbon nanotubes. Aniline and iron oxide were composited with each other, and aniline had good conductivity. Iron oxide could further improve the conductive network formed by polyaniline, thereby improving the conductivity of the modified multi-walled carbon nanotubes and further improving the antistatic properties of the aramid fiber.
[0107] Compared with Example 1, Example 6-7 shows that the amount of aniline added was changed when preparing modified multi-walled carbon nanotubes in Example 6-7. The resistivity of the aramid fiber treated with Example 6-7 is higher than that of the aramid fiber treated with Example 1, indicating that the amount of aniline added affects the performance of the aramid fiber. Aniline has good conductivity, polymerizes on the surface of the modified multi-walled carbon nanotubes, and composites with iron oxide to improve the conductivity of the modified multi-walled carbon nanotubes. When the amount of aniline added is too little, the improvement effect is weakened. When the amount of aniline added is too much, the aniline is prone to agglomeration, thereby affecting the formation of the conductive network in the oil agent.
[0108] Compared with Example 1, in Example 8-9, the concentrations of tetrabutyl titanate and aluminum chloride were changed when preparing the modified composite microspheres in Example 8-9. The breaking strength of the treated aramid fiber in Example 8-9 was lower than that of the treated aramid fiber in Example 1, and the resistivity was higher than that of the treated aramid fiber in Example 1. In Example 10-11, the concentrations of tetrabutyl titanate and aluminum chloride were changed, thereby changing the contents of Al2O3 and TiO2 in the Al2O3 / TiO2 hollow microspheres, thereby affecting the mechanical strength and microsphere morphology of the Al2O3 / TiO2 hollow microspheres, affecting the polymerization of pyrrole on the surface of the Al2O3 / TiO2 hollow microspheres, thereby affecting the morphology and polypyrrole content of the double-layer microspheres, and making the modified composite microspheres less effective in enhancing the mechanical strength and antistatic properties of aramid fibers.
[0109] Compared with Example 1, Example 10-11 shows that the amount of pyrrole monomer added is changed when preparing the modified composite microspheres in Example 10-11. The breaking strength of the treated aramid fiber in Example 10-11 is lower than that of the treated aramid fiber in Example 1, and the resistivity is higher than that of the treated aramid fiber in Example 1, indicating that the amount of pyrrole monomer added affects the performance of the aramid fiber. If the amount of pyrrole added is too low, the conductivity enhancement effect of polypyrrole on the Al2O3 / TiO2 hollow microspheres is reduced. If the amount of pyrrole added is too high, it is easy to cause self-aggregation and agglomeration of pyrrole, thereby reducing the formation of the polypyrrole layer outside the Al2O3 / TiO2 hollow microspheres, and the mechanical properties of the modified composite microspheres themselves are reduced, thereby reducing the enhancement of the antistatic and mechanical properties of the modified composite microspheres on the aramid fibers.
[0110] Compared with Example 1, Comparative Example 2-3 changes the mass ratio of modified multi-walled carbon nanotubes and modified composite microspheres in the composite conductive agent. The breaking strength of the aramid fiber treated in Comparative Example 2-3 is lower than that of the aramid fiber treated in Example 1, and the specific resistivity is higher than that of the aramid fiber treated in Example 1, indicating that the mass ratio of modified multi-walled carbon nanotubes and modified composite microspheres will affect the improvement of the mechanical strength and antistatic properties of the aramid fiber by the oil agent. Too little addition of modified multi-walled carbon nanotubes and modified composite microspheres will affect their enhancement effect on the mechanical properties of the aramid fiber. Too much addition will easily lead to agglomeration, resulting in poor dispersion of the modified multi-walled carbon nanotubes and modified composite microspheres, reduced breaking strength of the aramid fiber, affected the formation of the conductive network, and further affected the antistatic properties of the aramid fiber.
[0111] Compared with Example 1, Comparative Example 4-5 changes the mass ratio of the composite conductive agent, sodium sulfonated succinate and polyethylene glycol oleate in the antistatic agent. The specific resistivity of the aramid fiber treated in Comparative Example 4-5 is higher than that of the aramid fiber treated in Example 1, indicating that the mass ratio of the composite conductive agent, sodium sulfonated succinate and polyethylene glycol oleate affects the antistatic properties of the aramid fiber, and there is a synergistic effect among the composite conductive agent, sodium sulfonated succinate and polyethylene glycol oleate. In Example 1, the mass ratio among the three makes the synergistic effect of the composite conductive agent, sodium sulfonated succinate and polyethylene glycol oleate optimal, and the antistatic effect is better.
[0112] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high temperature resistant para-aramid spinning oil, characterized in that: The raw materials include the following weight percentages: smoothing agent 50-60%, high temperature resistant emulsifier 10-30%, high temperature resistant antioxidant 0.5-2%, antistatic agent 7-15%, high temperature resistant clustering agent 5-10%, high temperature resistant cosolvent 3-7%; The lubricant is pentaerythritol tetraisostearate and / or pentaerythritol tetrastearate; the antistatic agent comprises a composite conductive agent, sodium sulfosuccinate and polyethylene glycol oleate in a mass ratio of (0.5-0.7):(1.7-2.2):(1.5-1.8), and the composite conductive agent comprises modified multi-walled carbon nanotubes and modified composite microspheres in a mass ratio of (1-1.5):(0.9-1.2); The preparation method of the modified multi-walled carbon nanotubes comprises the following steps: adding polyethylene glycol and multi-walled carbon nanotubes modified by citric acid to a ferric nitrate solution, stirring evenly, shaking for 2-2.5 hours and slowly adding dilute ammonia water until the solution completely forms a precipitate, washing, drying, and calcining at 450-500° C. to obtain iron-loaded multi-walled carbon nanotubes; Disperse iron-loaded multi-walled carbon nanotubes in deionized water, perform ultrasonic dispersion until uniform dispersion, add aniline and perform ultrasonic dispersion for 30-35 minutes, stir in an ice-water bath and slowly drop an aqueous solution of ammonium persulfate into the mixture, allow to react for 12 hours, filter, wash and dry to obtain modified multi-walled carbon nanotubes; The modified composite microspheres are double-layer microspheres, the inner layer of the double-layer microspheres is Al2O3 / TiO2 hollow microspheres, and the outer layer of the double-layer microspheres is polypyrrole; the preparation method of the Al2O3 / TiO2 hollow microspheres is: adding polystyrene emulsion into anhydrous ethanol, ultrasonically dispersing until uniform, adding 8-10wt% tetrabutyl titanate and 4.3-5wt% aluminum chloride anhydrous ethanol solution, mixing evenly, and then slowly adding anhydrous ethanol solution containing ammonia water while stirring until the pH value is 10-10.2, reacting at 75-80°C for 5.8-6h, centrifuging, washing, and calcining at 480-500°C for 3-3.2h to obtain Al2O3 / TiO2 hollow microspheres.
2. The high temperature resistant para-aramid spinning oil according to claim 1, characterized in that: The mass ratio of the citric acid modified multi-walled carbon nanotubes to ferric nitrate is (0.17-0.2):(4.3-5), and the mass ratio of the iron-loaded multi-walled carbon nanotubes to aniline is (1-1.2):(9.5-10.2).
3. The high temperature resistant para-aramid spinning oil according to claim 1, characterized in that: The preparation method of the double-layer microspheres comprises the following steps: dispersing Al2O3 / TiO2 hollow microspheres in deionized water, adding pyrrole monomer, magnetically stirring for 30-40 minutes, then adding ferric chloride aqueous solution, magnetically stirring for 11-12 hours, centrifuging, filtering, washing and drying to obtain the double-layer microspheres.
4. The high temperature resistant para-aramid spinning oil according to claim 3, characterized in that: The mass ratio of the Al2O3 / TiO2 hollow microspheres to the pyrrole monomer is (1.8-2.2):(0.42-0.45).
5. The method for preparing a high temperature resistant para-aramid spinning oil according to any one of claims 1 to 4, characterized in that: The following steps are involved: Add pentaerythritol tetraisostearate and / or pentaerythritol tetrastearate, a high temperature resistant cosolvent and a high temperature resistant antioxidant into a reaction kettle, heat up to 70-90°C, stir for 1-2h, cool to 50-70°C, add a high temperature resistant emulsifier, an antistatic agent and a high temperature resistant sizing agent, stir until the mixture is uniform, cool to room temperature and filter.
Citation Information
Patent Citations
Sol-gel method for preparing earth silicon / titanic oxide hollow microballoon
CN101274246A
Antistatic spinning oil agent and preparation method thereof
CN111851073A
Stock solution oiling type para-aramid spinning oil
CN117587626A
Iron monatomic modified multi-walled carbon nanotube as well as preparation method and application thereof
CN118373414A